Research trajectory and future trends in curcumin related to immunity: a bibliometric analysis of publications from last two decades - Hong, Qing; Lyu, Wei; Zhang, Chaowei; Yao, Weiyi; Han, Yuxuan; Chen, Na (Frontiers in Immunology, 2025)
Curcumin has a clear immunopharmacological effect and plays an important role as an immune agent in various immune diseases and tumor immunotherapy. To comprehensively and scientifically clarify and reflect the development process, current status, and research trends of curcumin in the field of immune regulation, and to provide reliable insights for discipline development strategies and future research expansion, this study systematically analyzes 3939 valid articles related to curcumin and immunity published between 2004 and 2024 from the Web of Science database. Using Citespace and R-bibliometrix software for bibliometric analysis, we create visual knowledge maps from multiple dimensions including overall publication output, influential research entities, highly cited papers, research topics and hotspots. The results indicate that the overall number of publications and citations is currently in a rapid development phase. China occupies a core position in this research field but has low collaboration intensity. The Egyptian Knowledge Bank (EKB) is the institution with the highest publication volume. Moreover, cluster analysis reveals that research hotspots are gradually shifting from fundamental pathology to topics involving broad social and environmental influences. The top five keywords with the most explosive citations—curcumin, inflammation, apoptosis, oxidative stress, and cancer—represent the most focused and influential research topics. Currently, curcumin immunology has developed a diversified research perspective, accumulating significant research in the areas of active substance basis, pharmacological activity, anti-inflammatory, and anti-cancer studies. The thematic evolution trends and keywords related to curcumin’s immunological mechanisms summarized in this article provide insights and guidance for future research directions.